2009
DOI: 10.3148/70.4.2009.181
|View full text |Cite
|
Sign up to set email alerts
|

Coming and Going: Dietetic Students’ Experience of Their Education

Abstract: Acknowledging that an embodied curriculum has an impact on professionalization is important for educators and students because education is a critical site for developing a professional identity; this identity then influences how dietitians practise. This research has implications for recruitment language, professional practice curricula, faculty development, the scholarship of teaching and learning, and ongoing support for students as they enter practice contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 17 publications
2
45
0
2
Order By: Relevance
“…Females have been shown to be more interested in food and nutrition than males, which lead to the pursuit of nutrition‐related information and activities . Furthermore, a student's food and nutrition‐related activities plays an important function in the transformation from a novice into a professional dietitian . Consistent with previous research, the ND students in the present study reported having a primary interest in food and nutrition, sought nutrition information and followed dietary regimens.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Females have been shown to be more interested in food and nutrition than males, which lead to the pursuit of nutrition‐related information and activities . Furthermore, a student's food and nutrition‐related activities plays an important function in the transformation from a novice into a professional dietitian . Consistent with previous research, the ND students in the present study reported having a primary interest in food and nutrition, sought nutrition information and followed dietary regimens.…”
Section: Discussionsupporting
confidence: 86%
“…Pre‐existing knowledge and beliefs influence how individuals interpret and accept new information, and thus preconceived ideas dietetic students have about food and nutrition could influence their learning journey . Previous studies on this topic have consistently shown that individuals entering ND programs have a range of previous experiences with food, health and nutrition that contributes to their personal understanding . In addition, nutrition knowledge in community samples has been found to be influenced by age, gender, education and socio‐economic status, with educated females having the highest nutrition knowledge .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietetics educators in the present study were altruistic in their desire to make things better—both the educational experience of their students and the future profession. Their acknowledgement of being in a position to influence and shape the profession echoes the perspective previously shared by dietetics students and students in other health professions . Understanding dietetics educators’ drivers could be used to enhance their performance and productivity in workforce preparation and subsequently, that of the future workforce.…”
Section: Discussionmentioning
confidence: 86%
“…For the purpose of the present study, an ADEd is defined as a dietitian employed by a university who actively engages in the practice of educating and preparing entry‐level dietitian practitioners for the workforce in the university setting. As key stakeholders in dietetic workforce development, ADEds have the capacity to significantly influence future dietetic practitioners during the formative stages of their professional development …”
Section: Introductionmentioning
confidence: 99%